Diet-Induced Rodent Models of Diabetic Peripheral Neuropathy, Retinopathy and Nephropathy - Preguiça, Inês (2020)
Unhealthy dietary habits are major modifiable risk factors for the development of type 2 diabetes mellitus, a metabolic disease with increasing prevalence and serious consequences. Microvascular complications of diabetes, namely diabetic peripheral neuropathy (DPN), retinopathy (DR), and nephropathy (DN), are associated with high morbidity rates and a heavy social and economic burden. Currently, available therapeutic options to counter the evolution of diabetic microvascular complications are clearly insufficient, which strongly recommends further research. Animal models are essential tools to dissect the molecular mechanisms underlying disease progression, to unravel new therapeutic targets, as well as to evaluate the efficacy of new drugs and/or novel therapeutic approaches. However, choosing the best animal model is challenging due to the large number of factors that need to be considered. This is particularly relevant for models induced by dietary modifications, which vary markedly in terms of macronutrient composition. In this article, we revisit the rodent models of diet-induced DPN, DR, and DN, critically comparing the main features of these microvascular complications in humans and the criteria for their diagnosis with the parameters that have been used in preclinical research using rodent models, considering the possible need for factors which can accelerate or aggravate these conditions.